The Effects of Social Media on Afghan Students Learning English Speaking and Reading Skills (Journal of Social Sciences Review, 2023)
Social media (SM) not only serves as a means of entertainment but also plays a significant role in teaching, learning, and imparting new skills. As a result, a review has been proposed to determine the impact of SM sources on the improvement of English language proficiency at an intermediate level in Peshawar, Pakistan. This will be achieved by examining various articles and research papers on platforms such as Google Scholar and Research Gate. Among EFL instructors who must evolve outside the conventional methods of teaching where teachers used to complete most of the job, social media has garnered much respect and popularity. And speaking still gets less attention in conventional classrooms than writing and reading do. As a result, teaching speaking poses a significant challenge for both EFL teachers and students who exhibit poor oral achievement. Facebook and Google were the social networking sites most commonly used by college-level learners, according to the study's findings. The study also found that these sites had an impact on students' English language proficiency. As a result, the study suggests that its recommendations could benefit English teachers, curriculum developers, and textbook reviewers in promoting performance-based education. It is important to review what has been studied, what conclusions have been drawn, and what requires further attention. The study showed that social media can provide many advantages and functions in language learning, such as authentic input resources, low-stress practice spaces, opportunities for intercultural communication, and improved learner collaboration. However, the study also identified potential limitations of social media platforms, such as distractions and conflicting information. Finally, the study suggests several future research directions.
Keywords: Social Media; Facebook; Twitter; WhatsApp; Skype; TV; LinkedIn; Psychological Factors